THE EFFECTS OF TOPIRAMATE APPLIED TO THE NUCLEUS ACCUMBENS_x000D_ REGION ON MORPHINE WITHDRAWAL SYNDROME - YANANLI, HASAN RACİ; GÜLHAN, REZZAN (My University, 2020)
Aim: Nucleus accumbens, one of the nuclei of the basal ganglia, and dopamine, the neurotransmitter play a critical role in opioiddependence and withdrawal. In opioid withdrawal, the importance of neurotransmitters such as glutamate and gamma aminobutyric acid(GABA), as well as dopamine, is known. In this study, we aimed to investigate the effects of local injections of topiramate, anantiepileptic agent affecting GABAergic and glutamatergic pathways, into the nucleus accumbens on withdrawal signs and locomotoractivity during naloxone-induced withdrawal in morphine-dependent rats.Materials and Methods: Twenty male Sprague-Dawley rats were divided in topiramate treatment and control groups. All animalsreceived morphine pellets and guide cannulas were placed bilaterally in the nucleus accumbens regions by stereotaxic surgery. On thelast day of the experiment, following the bilateral topiramate or saline (control group) microinjections, morphine withdrawal was triggeredby naloxone.Results: Topiramate microinjections into the nucleus accumbens region significantly suppressed the signs of naloxone-inducedmorphine withdrawal such as number of jumpings and weight loss. No significant difference was observed in wet dog shakes, one of thewithdrawal signs, after local topiramate treatment. Although topiramate microinjections increased stereotypical activity it did not changelocomotor activity behavior such as vertical and ambulatory activity, and total covered distance.Conclusion: These findings show that local microinjection of topiramate into the nucleus accumbens is effective in preventing opioiddeprivation symptoms without significant effect on locomotor activity.

Amaç: Bazal gangliyon çekirdeklerinden biri olan nukleus akumbens ve nörotransmitter olan dopamin opioid bağımlılığı ve_x000D_ yoksunluğunda kritik rol oynamaktadır. Opioid yoksunluğunda dopaminin yanı sıra glutamat ve GABA gibi nörotransmitterlerin de önemi_x000D_ bilinmektedir. Biz bu çalışmada morfin bağımlılığı oluşturulan hayvanlarda GABAerjik ve glutamaterjik yolakları etkileyen antiepileptik_x000D_ ajan olan topiramatın nukleus akumbens bölgesine lokal uygulamasının naloksonla tetiklenen yoksunluk sendromunda yoksunluk_x000D_ bulguları ve lokomotor aktivite üzerine etkilerini araştırmayı amaçladık._x000D_ Materyal ve Metot: Yirmi adet erkek Sprague-Dawley sıçanları topiramat tedavi grubu ve kontrol grubu olarak ikiye ayrıldı. Hayvanların_x000D_ hepsine morfin peletleri uygulandı, stereotaksik cerrahi işlemle nukleus akumbens bölgelerine kılavuz kanüller bilaretal yerleştirildi._x000D_ Deneyin son gününde bilateral topiramat veya serum fizyolojik (kontrol grubu) mikroenjeksiyonlarını takiben nalokson uygulanarak morfin_x000D_ yoksunluğu tetiklendi._x000D_ Bulgular: Nukleus akumbens bölgesine lokal uygulanan topiramat naloksonla tetiklenen morfin yoksunluk bulgularından sıçrama_x000D_ sayısını ve ağırlık kaybını anlamlı düzeyde baskıladı. Lokal topiramat uygulaması yoksunluk bulgularından ıslak köpek silkinmesinde ise_x000D_ anlamlı değişiklik yapmadı. Topiramat mikroenjeksiyonları stereotipik hareketleri artırdığı halde vertikal hareketler, ambulatuvar_x000D_ hareketler ve toplam kat edilen mesafe gibi lokomotor aktivite davranışlarını değiştirmedi._x000D_ Sonuç: Bu bulgular antikonvülzan ilaç olan topiramatın nukleus akumbens bölgesine lokal uygulanmasının lokomotor aktivitede anlamlı_x000D_ baskılanma yapmadan opioid yoksunluk belirtilerinin önlenmesinde etkili olduğunu göstermektedir.
Nukleus Akumbens Bölgesine Uygulanan Topiramatın Morfin Yoksunluk Sendromuna Etkileri